Self and parent-proxy rated health-related quality of life (HRQoL) in youth with obesity: are parents good surrogates? - Ooi, Delicia Shu Qin (2022)
Purpose Consideration of health-related quality of life (HRQoL) and wellbeing outcomes is important to guide healthcare services for youth with obesity, yet youth perspectives may difer from their parents. This study compared youth and parental HRQoL reports and evaluated levels of concordance across HRQoL domains and as a function of youth age, youth gender and parent informant (mother and father).